2016
DOI: 10.1021/acssuschemeng.6b01765
|View full text |Cite
|
Sign up to set email alerts
|

Green Solid-Phase Peptide Synthesis 2. 2-Methyltetrahydrofuran and Ethyl Acetate for Solid-Phase Peptide Synthesis under Green Conditions

Abstract: N,N-Dimethylformamide (DMF), N-methyl-2-pyrrolidone, and dichloromethane (DCM) are the most widely used solvents for Fmoc solid-phase peptide synthesis (SPPS). These solvents are considered hazardous chemicals and are normally used in large amounts for washing, deprotection, and coupling steps. Therefore, the use of these reagents is indeed in question. Our group recently reported the use of 2-methyltetrahydrofuran (2-MeTHF), which is a green solvent, for coupling, but using DMF for the Fmoc removal and washin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 34 publications
1
91
0
Order By: Relevance
“…12,13 Whilst this paper was being written, the use of a mixture of 2-MeTHF and ethyl acetate for both coupling and Fmoc deprotection steps was reported. 18 However, in some cases elevated temperatures were required and the production of mixed solvent waste is undesirable as it complicates solvent recycling especially when the solvents have virtually identical boiling points (77 and 78°C for ethyl acetate and 2-MeTHF respectively). There are also a few reports of use of water as a solvent for solid-phase peptide bond formations using coupling agents 19 or enzymes 20 and of solvent free nonresin supported peptide synthesis by ball-milling.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Whilst this paper was being written, the use of a mixture of 2-MeTHF and ethyl acetate for both coupling and Fmoc deprotection steps was reported. 18 However, in some cases elevated temperatures were required and the production of mixed solvent waste is undesirable as it complicates solvent recycling especially when the solvents have virtually identical boiling points (77 and 78°C for ethyl acetate and 2-MeTHF respectively). There are also a few reports of use of water as a solvent for solid-phase peptide bond formations using coupling agents 19 or enzymes 20 and of solvent free nonresin supported peptide synthesis by ball-milling.…”
Section: Introductionmentioning
confidence: 99%
“…Ethyl acetate and ethanol are recommended in the CHEM21 guide, as is anisole in the ether solvent category and methyl ethyl ketone (MEK, 2‐butanone) in the ketone category. Previous researchers have reported the use of acetonitrile (MeCN), 2‐methyltetrahydrofuran (2‐MeTHF) and gamma‐valerolactone (GVL) as greener replacements for DMF and NMP in SPPS and demonstrated that ‘difficult’ peptides can be successfully synthesised when using the aforementioned greener solvents 15,25,46–48 . We have also reported the use of GVL and another green solvent Cyrene (dihydrolevoglucosenone) 49 as part of our previous studies involving the critical initial loading stage of SPPS 50 .…”
Section: Resultsmentioning
confidence: 99%
“…As described in the introduction, there has been a surge in interest in implementing green chemistry principles on SPPS in recent years, now termed greener solid‐phase peptide synthesis (GSPPS) . In line with the 5th principle of green chemistry and for comparison, we also attached Fmoc‐Gly‐OH onto RA‐MBHA resins using greener solvents.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the aforementioned issues, there has been an increase of interest within the peptide science community in the use of greener solvents for SPPS. Albericio, North, and Lopez recently reported successful synthesis of peptides using green SPPS strategies and proposed several different possible greener alternatives to DMF for solid‐phase synthesis . Despite these issues, DMF remains a popular solvent for fluorenylmethyloxycarbonyl‐based SPPS (Fmoc‐SPPS) and is likely to remain a popular solvent in academic settings for the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%